2013
DOI: 10.1103/physrevb.88.165139
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-controlled Ohmic to Schottky transition at a metal/ferroelectric interface

Abstract: and Tsymbal, Evgeny Y., "Polarization-controlled Ohmic to Schottky transition at a metal/ ferroelectric interface" (2013 Ferroelectric polar displacements have recently been observed in conducting electron-doped BaTiO 3 (n-BTO). The coexistence of a ferroelectric phase and conductivity opens the door to new functionalities that may provide a unique route for novel device applications. Using first-principles methods and electrostatic modeling, we explore the effect that the switchable polarization of n-BTO has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…The Fermi surface of n-BaTiO 3 consists of a single sheet forming a corrugated tube oriented along the electric polarization, as shown previously in Ref. [28]. The overlap between the Fermi surfaces of SrRuO 3 and n-BaTiO 3 , viewed along the transport direction, leads to the ringlike area approximately indicated by the concentric circles in Figs.…”
Section: Fig 1 (Color Online)mentioning
confidence: 77%
See 1 more Smart Citation
“…The Fermi surface of n-BaTiO 3 consists of a single sheet forming a corrugated tube oriented along the electric polarization, as shown previously in Ref. [28]. The overlap between the Fermi surfaces of SrRuO 3 and n-BaTiO 3 , viewed along the transport direction, leads to the ringlike area approximately indicated by the concentric circles in Figs.…”
Section: Fig 1 (Color Online)mentioning
confidence: 77%
“…The combination of ferroelectricity and conductivity in one material introduces unique electronic properties, opening the door to extended functionalities. In our previous work [28], we showed that the ferroelectric polarization can be used to alter the resistive nature of the interface between n-BaTiO 3 and metallic SrRuO 3 . Specifically, we found that polarization switching in n-BaTiO 3 induces a transition between Ohmic and Schottky regimes, leading to a 5-ordersof-magnitude change in interface resistance.…”
mentioning
confidence: 99%
“…20 shows how the change of injection barriers due to the inversion of polarization direction well explains the switch of rectification in V J  curves. Using an important PV model (Liu et al, 2013,Fang et al, 2014, we will note that this is the way in which the surface Schottky barriers are modified by poling. The change of the conduction band at the contact measured by an AFM tip is illustrated in Fig.…”
Section: Change Of Injection Barriers and Depolarization Fieldmentioning
confidence: 99%
“…In this case of thicker layers, the average potential barrier height across the ferroelectric layer is not the determining parameter for conduction and resistive switching can be obtained with symmetric electrodes. 17,25 Moreover, it is believed that the presence of vacancies and charged defects plays an important role determining conduction through the ferroelectric layers so that both polarization charges and defect charges need to be considered to understand the resistive switching phenomena in ferroelectrics. 8,[10][11][12][13][14][15]35 However, there does not seem to be a clear understanding about the relative importance of the two.…”
mentioning
confidence: 99%
“…2,7 Because of this, the interest on ferroelectric resistive switching has increased in recent years. [8][9][10][11][12][13][14][15][16][17][18] In order to take into account the polarization screening at the interfaces (or the so-called "dead-layer"), 19 one can consider the metal-ferroelectric junction to be a Schottky contact with the ferroelectric polarization modeled as a charged sheet at a certain distance of the physical interface with the electrode. 20,21 Assuming small (and non-overlapping) depletion layers, this model has given experimental Schottky barrier height (SBH) values in the range of ϕ o = 0.2-0.9 eV for various ferroelectrics and orientations.…”
mentioning
confidence: 99%